LYCOPODIACEAE DI KAWASAN SICIKE-CIKE, SUMATRA UTARA - Sri Hartini (Universitas Pakuan, 2015)
Research of Lycopodiaceae has been done in the area of forest Sicike-cike, North Sumatra. Research conducted in April 2011 with an exploratory method. Based on the results of the research there are 6 types of Lycopodiaceae found in this district namely Lycopodiella cernua, Huperzia phlegmaria, Huperzia carinata, Huperzia prolifera, Huperzia dalhousieana and Huperzia squarrosa. Lycopodiella cernua is the only type that grow terrestrial trunk that extends the length of the other 5 types, are being grown in a trunk dangling epiphyte. Huperzia carinata and Huperzia prolifera has a similar stature, Huperzia dalhousieana, was similar to that of Huperzia squarrosa. Huperzia phlegmaria is the only type that has the area between the sterile and part fertile clearly visible, are other types of area between the sterile and part fertile there is a gradual change.Â Key words: Lycopodiaceae, Sicike-cike, North Sumatra